(untitled) (KONFERENSIYA, 2025)
This study explores the benefits and challenges of integrating authentic texts, audio, and video materials into practical translation as a means of enhancing language learning. Authentic resources expose learners to real-world linguistic patterns, idiomatic usage, and diverse registers, thereby enriching their linguistic competence. They also foster intercultural awareness, pragmatic understanding, and professional readiness by simulating real translation contexts. Moreover, the inclusion of audio-visual materials promotes multimodal skills such as subtitling and dubbing, aligning with the demands of the modern translation market